Training with tarantulas: A randomized feasibility and acceptability study using experiential learning to enhance exposure therapy training. (December 2020) - Frank, Hannah E.; Becker-Haimes, Emily M.; Rifkin, Lara S.; Norris, Lesley A.; Ollendick, Thomas H.; Olino, Thomas M.; Kratz, Hilary E.; Beidas, Rinad S.; Kendall, Philip C.
Highlights: Therapists received training-as-usual (TAU) or experiential training in exposure. Therapists receiving experiential training underwent exposures themselves. Experiential training was found to be feasible and acceptable. Experiential training led to greater use of exposures than TAU. Abstract: Background: Although exposure is a key evidence-based intervention for anxiety, it is infrequently used in clinical settings. This study employed a novel training strategy, experiential learning, to improve exposure implementation. This study aimed to assess the feasibility and acceptability of experiential training and preliminary training effectiveness. Methods: Participants were 28 therapists who were randomized to (a) training-as-usual or (b) experiential training (training-as-usual plus a one-session treatment for fear of spiders). Workshops lasted one day and were followed by three months of weekly consultation. Results: Experiential training was viewed as feasible and acceptable. Participants, including those who were fearful of spiders, had a positive response to the training and reported it to be useful. There was a significant increase in the number of exposures used by therapists receiving experiential training compared to training-as-usual at 1-month follow-up. Conclusions: A one-day training resulted in significant improvements in knowledge, attitudes toward exposure, and self-efficacy in using exposure. Preliminary findings suggest that experiential training resulted in greater use of exposure post-training compared to training-as-usual. Results provide evidence for the feasibility and acceptability of experiential training as a strategy to increase the use of evidence-based interventions.